DIPLOMASI EKONOMI INDONESIA TERHADAP INDIA DALAM MENYIKAPI KETIDAKPASTIAN KEBIJAKAN TARIF MASUK CRUDE PALM OIL (CPO) PERIODE 2017-2020 - Agustinus Renaldi Indiarto (2022)
Indonesia is the largest producer of CPO in the world. This causes CPO to become one of Indonesia's leading commodities for trading with various countries such as India. India is a potential market for Indonesia's CPO commodities. This is due to the increasing demand for vegetable oil in India, especially CPO. However, when the Indian government set an uncertain CPO import tariff policy since 2017, it tends to decrease the quantity and value of Indonesia's CPO exports to India in 2017-2020. Therefore, it becomes a tariff barrier for Indonesia's CPO commodity trade. Based on these conditions, this study aims to analyze how Indonesia's economic diplomacy efforts towards India in responding to the uncertainty of the CPO import tariff policy for the 2017-2020 period. This study is descriptive qualitative and uses several data collection techniques such as document-based research, internet-based research, and interview. In addition, this study uses an interactive model data analysis technique that was designed by Matthew B. Miles, A. Michael Huberman, and Johnny Saldaña. Based on the result of the study, it shows several ways of Indonesia's economic diplomacy towards India in responding to the uncertainty of the CPO import tariff policy for the 2017-2020 period at government to government and government to business levels. Despite any number of challenges, Indonesia has succeeded in reducing CPO import tariffs by 16,5% in the 2017-2020 period.